Prevalence Of Hypodontia In Patients Attending Orthodontic Clinic In Kuala Terengganu - Shakirah Said, Salma; Abdul Rahim, Farah Salwa; Jaapar, Mustaffa (IIUM Medical Journal Malaysia, 2017)
Introduction: The objective of this study was to determine the prevalence and the pattern of hypodontia among orthodontic patients in Klinik Pergigian Jalan Sultan Mahmud, Kuala Terengganu. Materials and Methods: A retrospective of 351 orthodontic patients record review study was conducted; comprised of 104 males and 247 females. The records were reviewed by trained dental officer between October 2016 and June 2017. The Chi-square and Fisher’s Exact Tests were carried out for statistical analysis. Results: The prevalence of hypodontia was 10.8%. Thirty-eight patients were found to have at least single missing tooth. A significant difference was found between males and females of having hypodontia (p = 0.048). No significant difference was found for hypodontia patients by races (p = 0.829). The maxillary lateral incisor was the most frequently missing tooth followed by mandibular second premolars and mandibular lateral incisors. Hypodontia cases observed tended to be more likely occurred in the upper left arch compared to the lower arch. The majority of hypodontia patients had single missing tooth, but rarely more than 3 missing teeth. Hypodontia patients had mainly Class III malocclusion, however no statistically significant was found (p= 0.081). Conclusion(s): The prevalence of hypodontia of this study was within the range of what is being reported in the literature and showed gender significant. Hypodontia was mainly involved maxillary lateral incisors; more prevalent in the upper arch; and mostly observed in patients with Class III malocclusion in the study sample. Early detection and accurate diagnosis are essential. Therefore, alternative treatment modalities can be well planned under multidisciplinary team approach in restoring the aesthetic and function.